High-tech element availability for sustainable energy systems in the 21st century : The Iberian Pyrite Belt as a potential supplier - Reiser, Fiona K. M. (2010)
This work provides estimations on the future raw material demand for the thin-film photovoltaic (PV) elements indium, selenium, tellurium, germanium and gallium. Data calculation has been carried out on the basis of current energy and PV market outlooks. For indium, our calculation yields a maximum cumulative demand of 12 kilotons for the period from 2008 to 2030. The minimum demand for the same period is of 8 kilotons. Additionally, static depletion times for the elements in question have been determined. For indium, the static depletion time of 22 years shows that its supply is highly endangered, particularly if indium consumption for LCD and solar panel production stays on a high level or even increases. The situation for selenium, with a static depletion time of 53 years, is not much better. Therefore, in addition to recycling, the fundamental way to enhance material supply is through intensified exploration for mineral deposits. Such exploration could focus in promising areas, where high-technology elements are already known to exist in sulphide ore deposits, e.g. the Iberian Pyrite Belt (IPB), a metallogenic province known for its massive sulphide ore resources.